The Effect of Planting Space and Harvesting Period on Dry Matter Production of Edamame Soybean Straw in Samigaluh, Kulonprogo, Yogyakarta, Indonesia - Umami, Nafiatul (2014)
This research was conducted in Samigaluh, Kulon Progo, Yogyakarta , aiming to obtain data on the effect of the addition of rhizobium inoculum and on the productivity of Edamame soybean straw. The objectives of this research were to determine the effect of plant spacing and harvesting period on the growth and production of Edamame soybean hay (Glycini max). The spacing treatments were 20 cm x 20 cm (J1) and 20 cm x 50 cm (J2), while the harvesting period treatments were 65 days (UP1) and 78 days (UP2). Each planting medium was 2 x 2,5 wich was added by basic fertilizer, i.e. manure . Replication of this research was conducted three times. After 3 weeks, Edamame soybean plants were given urea (50kg/ha), K fertilizer (25 kg/ha), and P fertilizer (45 kg/ha). The soil used as the growing media of edamame soybeans was latosol type. The observations included Edamame soybean growth (vegetative and reproductive), and dry matter production as well as organic matter production of Edamame soybean hay and pods. The data obtained were analyzed using a completely randomized design (CRD) factorial 2 x 2. If there were differences, the test was then followed by Duncan 's new multiple range test (DMRT). The results of the study showed that that treatment of plant spacing did not significantly affect plant growth stadia of Edamame soybean, both vegetative and reproductive stadia. Dry matter productions of Edamame soybean straw for difference (P < 0.01) were J1UP10.58 tons/ ha, J2 UP1 0.43 tons/ha, J1UP2 1.64 tons/ ha , and J2UP2 0.88 tons/ ha. Differences in plant spacing and harvesting period affected dry matter production of hay, and also the organic matter production of hay (P < 0.05). In 78 day harvesting period (UP2) the dry matter production of Edamame soybean hay and pods was higher than in 65 day harvesting period (UP 1).